Transcriptome-wide dynamics of m6A methylation in ISKNV and Siniperca chuatsi cells infected with ISKNV - Qijin Miao; Jing Jiang; Siyou Huang; Jie Gao; Qingqing Liu; Rui Zheng; Yiling Kang; Changjun Guo; Jianguo He; Junfeng Xie (BMC Genomics)
Abstract Infectious spleen and kidney necrosis virus (ISKNV) is a highly virulent and rapidly transmissible fish virus that poses threats to the aquaculture of a wide variety of freshwater and marine fish. N6-methyladenosine (m6A), recognized as a common epigenetic modification of RNA, plays an important regulatory role during viral infection. However, the impact of m6A RNA methylation on the pathogenicity of ISKNV remains unexplored. Here, methylated RNA immunoprecipitation sequencing (MeRIP-seq) coupled with RNA sequencing (RNA-seq) was used to systematically detect variations in m6A methylation and gene expression between ISKNV-infected and noninfected MFF-1 cells, followed by functional enrichment and co-expression joint analysis. The findings revealed that the m6A methylation peaks were located mainly in coding sequences (CDSs), with more than 90% of the transcripts containing 1–5 m6A peaks. Through MeRIP-seq, 4361 differentially m6A-methylated mRNAs were identified. Gene enrichment analysis revealed that m6A-related genes were enriched in biological processes and pathways such as gene expression, cellular structure, immune responses, and cell death. Co-expression analysis revealed that the genes differentially expressed at both the mRNA and m6A modification levels were enriched in pathways such as the hippo, ErbB, and JAK-STAT pathways. The m6A modification at the genome-wide transcription level of ISKNV was subsequently shown to be pronounced in several pivotal genes, such as putative vascular endothelial growth factor, ribonucleotide reductase small subunit, and E3 ubiquitin ligase. This study comprehensively describes the m6A expression profile in ISKNV- and ISKNV-infected MFF-1 cells, providing a basis for investigating the role of m6A modification during ISKNV infection.